2013
DOI: 10.1016/j.lfs.2013.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Anosmia does not impair the anxiolytic-like effect of lavender essential oil inhalation in mice

Abstract: These results suggest that olfactory system activation is unlikely to participate in the anxiolytic-like effect of lavender essential oil inhalation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…The anxiolytic effect of pure linalool (Umezu and others ) and its derivative linalool oxide (Souto‐Maior and others ) was verified in a small number of studies in rats. Greater attention was paid to these properties in lavender essential oils, where linalool and other terpene alcohols are major components (Bradley and others , ; Chioca and others ) than in a commercial lavender preparation, Silexan (Woelk and Schlafke ; Kasper and others ).…”
Section: Sedative Effectsmentioning
confidence: 99%
“…The anxiolytic effect of pure linalool (Umezu and others ) and its derivative linalool oxide (Souto‐Maior and others ) was verified in a small number of studies in rats. Greater attention was paid to these properties in lavender essential oils, where linalool and other terpene alcohols are major components (Bradley and others , ; Chioca and others ) than in a commercial lavender preparation, Silexan (Woelk and Schlafke ; Kasper and others ).…”
Section: Sedative Effectsmentioning
confidence: 99%
“…The inhalation procedure described by Chioca, Antunes, Ferro, Losso, and Andreatini () and Chioca, Ferro, et al () was used. Briefly, the mice were kept for 15 min in a plastic recipient with lid (32 × 24 × 32 cm) exposed to different concentrations of the C. sinensis essential oil (1%, 2.5%, 5%, and 10%), in a volume of 1 ml soaked in cotton wool, which was previously weighed (0.7 g).…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6] We recently found that in vivo transferability by inhalation administration varies depending on the type of volatile compounds. It has been reported that essential oils of coniferous trees, juniper, lavender and sandalwood have anxiolytic-like activities, and the chemical components exhibiting these effects are reported to be linalool, linalyl acetate, a-pinene and a-santalo.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that essential oils of coniferous trees, juniper, lavender and sandalwood have anxiolytic-like activities, and the chemical components exhibiting these effects are reported to be linalool, linalyl acetate, a-pinene and a-santalo. [1][2][3][4][5][6] We recently found that in vivo transferability by inhalation administration varies depending on the type of volatile compounds. 7 For example, 1,8-cineole is not readily metabolized from within the brain, even at 30 min after inhalation.…”
Section: Introductionmentioning
confidence: 99%